Selling technology : the changing shape of sales in an information economy - Darr, Asaf. (Ithaca : Cornell University Press, 2006)
"Asaf Darr's ethnographic exploration of the sales process for standard and emergent technology argues that our cultural stereotypes of sales work and salespeople, shaped during the industrial era and through popular images of the Yankee peddler and the car salesman, no longer apply to the changing nature of sales in an information economy."
"In the high-technology settings in which cutting-edge artifacts are traded, Darr finds that sales work deviates sharply from our traditional cultural images. The educational level and technical skills of the sales force are increasing, sellers' and buyers' engineers engage in codevelopment, and long-term collaborative relationships are replacing brief sales encounters. A growing number of work tasks and skills previously performed and mastered in the design or production phases have become part of the sale of emergent technology. New control mechanisms over the work of the sales engineers are also appearing
Unlike most enthographic studies of salespeople, which focus on the insurance, finance, and retail sectors, Darr's book turns to the daily sales practices of an information economy."--Jacket
Sales work in culture and practice -- Sellers, buyers, and market organization -- Searching for clients and constructing sales ties in a mass market -- Searching for clients and constructing sales ties in emergent technology markets -- Maintaining sales ties in a mass market -- Maintaining sales ties in emergent technology markets -- The changing nature of sales work.
Includes bibliographical references (pages 133-138) and index.
Print version record.
JSTOR
Keywords: Selling -- High technology; Selling -- Technological innovations; Selling -- Social aspects; Information technology -- Social aspects; Technologie de pointe -- Vente; Vente -- Innovations; Vente -- Aspect social; Technologie de l'information -- Aspect social; SOCIAL SCIENCE -- Sociology -- General; Information technology -- Social aspects; Selling -- High technology; Selling -- Social aspects; Selling -- Technological innovations; Spitzentechnologie; Verkaufstechnik; Verkooptechnieken; Sociale aspecten; Technologie